1935
DOI: 10.1002/prac.19351430108
|View full text |Cite
|
Sign up to set email alerts
|

Magnetochemische Untersuchungen, XIV. Das magnetische Verhalten einiger Schwermetallverbindungen des Phthalocyanins

Abstract: I. Allgemeines u n d P r o b l e m s t e l l u n g Kiirzlich ist von R. P. L i n s t e a d und Mitarbeitern z, eine neue Klasse von tief farbigen Stoffen entdeckt worden, die Phthalocyanioe, von denen z. B. der Kupferverbindung die For-me1 I zuzuteilen ist. Die Schwermetallverbindungen des Phthalo-~ cyanins zeichneu sich durch eine auBerordentliche Bestandigkeit aus. So la& sich z. B. das Kupfersalz CuC,,R,,N, sowohl im Hochvakuum wie im indifferenten Gasstrom unzersetzt sublimieren, wobei man Hartglas oder Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1935
1935
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The magnetic properties of tetrapyrrolic metal complexes (Figure ) have been widely studied, beginning with measurements on metallophthalocyanines made by Klemm and Klemm in 1935 . Among neutral insulating complexes, the square-planar geometry is perhaps the most magnetically interesting.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic properties of tetrapyrrolic metal complexes (Figure ) have been widely studied, beginning with measurements on metallophthalocyanines made by Klemm and Klemm in 1935 . Among neutral insulating complexes, the square-planar geometry is perhaps the most magnetically interesting.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying the electronic configuration under given environments is therefore the most essential starting point for further understandings and applications of the magnetic anisotropy of these compounds, stimulating intensive studies in this direction. An earlier study 7 reported its spin multiplicity being in between S = 1~2 7 . Later, Dale et al .…”
Section: Introductionmentioning
confidence: 99%
“…At lower temperatures the curves diverge: while the ␤-FePc behaves as a singlet-ground-state paramagnet down to the lowest temperatures, [11][12][13][14] the ␣-FePc susceptibility increases rapidly with decreasing temperature in close resemblance to the Ising linear chain behavior down to about 10 K. 7 Below 10 K the ac susceptibility and magnetization data proved the existence of ferromagnetism, although the long range ordering peak could not be evidenced from heat capacity experiments, not very surprisingly in view of the very fine powder form of the sample and the chainlike magnetic behavior. However, an interesting feature remains unexplained.…”
Section: Introductionmentioning
confidence: 99%